Effect of frozen storage on the chemical and sensory properties of red tilapia (Oreochromis niloticus) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Tilapia is one of the fastest growing aquaculture productions in the world and understanding of its storage to ensure the quality of the fish before the product reaches consumer is important. Freezing changes a food physical state by changing water into ice when energy is removed in the form of cooling below freezing temperature and its effect on the quality of fish is widely studied. This present study evaluated the effect of frozen storage of tilapia fillet at -18°C over 120 days. The study revealed that all the chemical quality indices studied like pH (6.60±0.02 to 6.98±0.05), TVB-N (11.81±0.03 N/100g to 22.98±0.18 N/100g), TBA (0.03±0.02 mg malondialdehyde/Kg to 0.18±0.06 mg malondialdehyde/Kg) and PV (0.02±0.00 mEq/kg to 0.80±0.07 mEq/kg) increased in value over the 120 days of storage period. Meanwhile the sensory attribute of the fillet decreased for all parameters evaluated, but were still considered acceptable at the end of the storage period.
Keywords: tilapia; oxidation; sensory evaluation; frozen storage